Evaluation Techno-economic of Ice Thermal Energy Storage for Office Building in Libya - Mohamed Mustafa M. Abdulgalil,; Ali M. Abdoulha Massoud, (African Journal of Advanced Pure and Applied Sciences, 2024)
This study evaluates the Techno-economic of ice thermal storage (ITS) system for office building in Libya for decreasing power consumption. The (ITS) is integrated into the conventional air conditioning system to reduce the cost of cooling an office building. The Techno-economic of the partial ice thermal storage cooling system was studied by comparing the cost savings of this system to the conventional systems assuming several economic scenarios in which the costs of conventional and backup energy were considered. Results presented in the term of saving energy amount, consumption energy and payback period. Based on the results obtained, it was found that the cooling cost decreased with increasing storage capacity. In addition, the most amount of the stored energy should be used in electricity peak hours as much as possible to increase cooling costs. To achieve great results in a payback period for alternative systems, the price of electricity in Libya between day and night should be increased by four times from the current level during the day time and the demand charges should be taken in account in tariff electricity.